2006
DOI: 10.1159/000095131
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Induces Anion Conductance and Cytosol-To-Membrane Transposition of ICln in INS-1E Rat Insulinoma Cells

Abstract: The metabolic coupling of insulin secretion by pancreatic beta cells is mediated by membrane depolarization due to increased glucose-driven ATP production and closure of KATP channels. Alternative pathways may involve the activation of anion channels by cell swelling upon glucose uptake. In INS-1E insulinoma cells superfusion with an isotonic solution containing 20 mM glucose or a 30% hypotonic solution leads to the activation of a chloride conductance with biophysical and pharmacological properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…However, the unexpected effect of carbenoxolone can be explained by that this compound has been described as a potent inhibitor of volume-regulated anionic channels also known as VRACs [16]. There is an accumulating body of evidence that the VRAC is involved in the nutrient-sensing mechanism of the pancreatic beta cell, as both glucose [17,18] and fatty acids [18] have been shown to cause VRAC activation. While the molecular identity of the VRAC is still unknown, it has been suggested as a critical component in an alternate route for depolarization of the pancreatic beta cell [19], a route that is independent of metabolic coupling and subsequent activation of K ATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the unexpected effect of carbenoxolone can be explained by that this compound has been described as a potent inhibitor of volume-regulated anionic channels also known as VRACs [16]. There is an accumulating body of evidence that the VRAC is involved in the nutrient-sensing mechanism of the pancreatic beta cell, as both glucose [17,18] and fatty acids [18] have been shown to cause VRAC activation. While the molecular identity of the VRAC is still unknown, it has been suggested as a critical component in an alternate route for depolarization of the pancreatic beta cell [19], a route that is independent of metabolic coupling and subsequent activation of K ATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to hypotonic cell swelling, no significant RVD is evident during glucoseinduced cell swelling [66,67]. The fact that glucoseinduced insulin secretion is completely blocked at conditions when swelling-induced secretion is active (such as Ca 2+ depletion, MPA and BEL treatment) shows that swelling does not play important role in glucose-stimulated insulin release.…”
Section: +mentioning
confidence: 98%
“…It is of interest that rising of glucose concentration in the medium also increases rat pancreatic β [66] or insulinoma cell [67] volume. In contrast to hypotonic cell swelling, no significant RVD is evident during glucoseinduced cell swelling [66,67].…”
Section: +mentioning
confidence: 99%
“…These currents are activated by cell swelling in response to glucose uptake or exposure to a hypotonic medium (referred to as ICl swell , ICl glucose or ICl islet ) and by intracellular ATP and other adenosine nucleotides [5][6][7][8][9][10]. In a previous work we provided evidence that ICl glucose and ICl swell are identical currents and found that glucose uptake induces a volume increase sufficient to activate the conductance in INS-1E rat insulinoma cells [11]. Importantly, Cl -efflux depolarizes the cell membrane which contributes to K ATP channel-independent triggering of insulin release upon cell swelling.…”
Section: Introductionmentioning
confidence: 99%